Postoperative hip center position is associated with gait symmetry in range of axial rotation in dysplasia patients after THA - Hu, Yi; Zou, Diyang; Jiang, Mengda; Qian, Qingyu; Li, Huiwu; Tsai, Tsung-Yuan; Zhang, Jingwei (Frontiers in Surgery, 2023)
Background: This study aimed to explore whether pre- or postoperative hip structures or surgical changes significantly influence hip range of motion (ROM) symmetry in patients with hip dysplasia during gait after total hip arthroplasty (THA) and provide possible surgical suggestions. Methods: Fourteen patients with unilateral hip dysplasia underwent computed tomography before and after surgery to create three-dimensional hip models. Pre- and postoperative acetabular and femoral orientations, hip rotation centers (HRC), and femoral lengths were measured. Bilateral hip ROM during level walking after THA was quantified using dual fluoroscopy. The ROM symmetry in flexion-extension, adduction-abduction, and axial rotation was calculated using the symmetry index (SI). The relationship between SI and the above anatomical parameters and demographic characteristics was tested using Pearson’s correlation and linear regression. Results: The average SI values for flexion-extension, adduction-abduction, and axial rotation during gait were -0.29, -0.30, and -0.10, respectively. Significant correlations were detected mainly in the postoperative HRC position. A distally placed HRC was associated with increased SI values for adduction-abduction (R=-0.47, p=0.045), while a medially placed HRC was associated with decreased SI values for axial rotation (R=0.63, p=0.007). A regression analysis indicated that horizontal HRC positions significantly determined axial rotational symmetry (R2=0.40, p=0.015). Normal axial rotation SI values were achieved with HRC between 17 mm medially and 16 mm laterally. Conclusions: Postoperative HRC position was significantly correlated with gait symmetry in the frontal and transverse planes in patients with unilateral hip dysplasia after THA. Surgical reconstruction of the HRC to between 17 mm medially and 16 mm laterally may contribute to gait symmetry.